Competitiveness and concentration of the banking sector as a measure of banks’ credit ratings - Chodnicka-Jaworska, Patrycja (Research Papers of Wrocław University of Economics, 2018)
The aim of the paper is to verify the impact of the competitiveness of the banking sector and concentration on banks’ credit ratings. A literature review was carried out and as a result the following hypothesis was put forward: the bigger the banks from the countries where the banking sector is more concentrated and more competitive, the higher the banks’ credit ratings. The analysis was conducted using ordered panel data models on banks’ credit ratings with the use of quarterly data on a European banks’ sample. Long-term issuer credit ratings given to banks by the three largest credit rating agencies were used as a dependent variable
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 26-39
Keywords: credit rating; panel data models; concentration; competitiveness; ocena wiarygodności kredytowej; modele danych paneli; koncentracja; konkurencyjność